Local Prior Employment and Ecosystem Dynamics. (October 2019) - Clayton, Paige; Donegan, Mary; Feldman, Maryann; Forbes, Allison; Lowe, Nichola; Polly, Alyse
This article utilizes a unique database (PLACE, the PLatform for Advancing Community Economies) to explore relationships between founders' prior work experiences and the outcomes of their entrepreneurial firms. The authors capture and compare multiple, intersecting, often overlapping, prior work experiences and assess their differential interactions within a local ecosystem. They augment existing empirical research, which has looked most closely at the impact of prior employment on firm financing and survival, to include labor market effects. Results show important differences in firm-level employment outcomes across prior work experiences, with an advantage accruing to founders with prior work experience in local life science firms.